Pengembangan Sistem Monitoring Getaran Mesin Berbasis Internet of Things Menggunakan Sensor MPU6050 dan ESP8266 - Ramadhani; Ichsan; muliakausar (J-Innovation, 2016)
Machine vibration monitoring is an important activity for identifying early indications of mechanical degradation, reducing unexpected failures, and supporting maintenance decisions. This study aims to design and evaluate an Internet of Things (IoT)-based machine vibration monitoring application using an MPU-6050 accelerometer, ESP8266 NodeMCU, TCP/IP communication, and MATLAB graphical user interface. The system was developed through the ADDIE model, which covers need analysis, system design, prototype development, implementation, and evaluation. Vibration acceleration data were acquired wirelessly from the sensor node, displayed in real time, and processed to obtain Root Mean Square (RMS), peak, peak-to-peak, average value, and machine condition status. Testing was conducted on four objects, namely a hand grinder, hand drill, kitchen blender, and water pump, with a monitoring duration of five minutes for each object. The test results showed RMS values of 0.86 m/s² for the hand grinder, 3.60 m/s² for the hand drill, 0.86 m/s² for the kitchen blender, and 0.71 m/s² for the water pump. These results indicate that the developed prototype is able to acquire, transmit, visualize, and classify vibration data as an initial reference for machine condition monitoring. However, further validation using industrial vibration measurement instruments is required to improve accuracy and reliability